2006
DOI: 10.1113/jphysiol.2006.115600
|View full text |Cite
|
Sign up to set email alerts
|

Central chemoreceptors and sympathetic vasomotor outflow

Abstract: The present study explores how elevations in brain P CO 2 increase the sympathetic nerve discharge (SND). SND, phrenic nerve discharge (PND) and putative sympathoexcitatory vasomotor neurons of the rostral ventrolateral medulla (RVLM) were recorded in anaesthetized sino-aortic denervated and vagotomized rats. Hypercapnia (end-expiratory CO 2 from 5% to 10%) increased SND (97 ± 6%) and the activity of RVLM neurons (67 ± 4%). Injection of kynurenic acid (Kyn, ionotropic glutamate receptor antagonist) into RVLM o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
118
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 57 publications
16
118
3
4
Order By: Relevance
“…Similarly, MRS2179 also decreased peripheral chemoreceptor activation of PNA amplitude and frequency by 25±6% (P=0.037; Figure 2A and 2E) and 33±7% (P=0.032; Figure 2A and 2F), respectively. Consistent with previous evidence, 36 bilateral RVLM injec tions of kynurenic acid decreased baseline PNA amplitude by guest on August 12, 2014 http://hyper.ahajournals.org/ Downloaded from (59±5%) and increased PNA frequency (46±4%), but did not affect sSNA or MAP. Injections of kynurenic acid into the RVLM also blunted the peripheral chemoreceptor-mediated increase in breathing amplitude, SNA, and blood pressure (Figure 2A, 2C-2F).…”
Section: Purinergic Signaling In the Rvlm Contributes To Peripheral Csupporting
confidence: 78%
See 2 more Smart Citations
“…Similarly, MRS2179 also decreased peripheral chemoreceptor activation of PNA amplitude and frequency by 25±6% (P=0.037; Figure 2A and 2E) and 33±7% (P=0.032; Figure 2A and 2F), respectively. Consistent with previous evidence, 36 bilateral RVLM injec tions of kynurenic acid decreased baseline PNA amplitude by guest on August 12, 2014 http://hyper.ahajournals.org/ Downloaded from (59±5%) and increased PNA frequency (46±4%), but did not affect sSNA or MAP. Injections of kynurenic acid into the RVLM also blunted the peripheral chemoreceptor-mediated increase in breathing amplitude, SNA, and blood pressure (Figure 2A, 2C-2F).…”
Section: Purinergic Signaling In the Rvlm Contributes To Peripheral Csupporting
confidence: 78%
“…Specifically, we show in anesthetized rats that bilat eral injections of kynurenic acid significantly decreased the ventilatory, sympathetic, and pressor responses to peripheral chemoreceptor activation. These results are consistent with pre vious studies that used kynurenic acid 36 or APV ([2R]amino5 phosphonovaleric acid; specific Nmethyldaspartate receptor blocker) 48 to attenuate the response of RVLM presympathetic cells to peripheral chemoreceptor drive. In addition, we found that the majority of NTS terminals in the RVLM were immuno reactive for VGLUT2 (77%).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…3) localização e exposição do nervo frênico e do nervo esplâncnico via posição dorsolateral (MOREIRA et al, 2006;MOREIRA, 2013;TAKAKURA et al, 2006;TAKAKURA et al, 2008;TAKAKURA et al, 2007) …”
Section: Procedimentos Cirúrgicos Em Animais Anestesiadosunclassified
“…Embora seja crescente o número de trabalhos postulando que núcleos de células quimiossensíveis estejam distribuídos ao longo do encéfalo (Nattie, Li, 2010), é comumente aceito que o núcleo retrotrapezóide (RTN), localizado na porção ventral ao núcleo motor do núcleo facial e próximo da superfície ventrolateral do bulbo (Connelly et al, 1989;Connelly et al, 1990;Mulkey et al, 2004;Takakura et al, 2006), concentre o principal grupamento de células quimiorreceptoras centrais. Além disso, essa região está localizada próxima do grupamento catecolaminérgico C1 (Mulkey et al, 2004;Moreira et al, 2006;Lazarenko et al, 2009). Esta organização anátomo-funcional sugere uma integração entre o quimiorreflexo periférico e central, a regulação da respiração e funções autônomas (Rosin et al, 2006;Takakura et al, 2006).…”
Section: Grupamento Adrenérgico C1 E O Controle Respiratóriounclassified